EFEKTIVITAS PERILAKU CERDIK DAN PATUH CEGAH STROKE BERULANG - Fransiska Anita Ekawati Rahayu Sapang; Yunita Carolina; Anita Sampe; Felisima Ganut (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2021)
The impact of recurrent stroke is heavier than the first attack because it increases mortality and disability which adds to the economic burden, decreases the quality of life of post-stroke patients. Lifestyle changes that cause recurrent stroke have an impact on reducing human resource productivity. The government program through GERMAS, namely CERDIK and PATUH programs was modified by researchers to prevent recurrent strokes by behaving in a healthy behavior used online and offline booklet media. This study aims to determine the effectiveness of providing health education on the CERDIK and PATUH lifestyle to prevent recurrent stroke in post-stroke patients. This research design was quasi-experiment pre and post-test without control. Sampling was done using the non-probability sampling technique by accidental sampling. The sample in this study amounted to 20 respondents. The questionnaire used was the questionnaire on the health behavior of CERDIK and PATUH to prevent recurrent strokes and the risk form for stroke events. The statistic test used Wilcoxon with the value of p=0.002 (p < 0.05) which means there is an effect of education on the behavior of stroke sufferers in preventing recurrent stroke. Then the risk of stroke event with the value of p=0.001 (p < α) which means there is an effect of education on preventing the risk of recurrent stroke. Therefore, it is hoped that post-stroke patients can be given health education on the CERDIK and PATUH behavior to prevent recurrent strokes.